Adopsi Inovasi Beauveria Bassiana di Desa Wirowongso Kecamatan Ajung Kabupaten Jember - Muhammad Iqbal Sufi'ad (Program Studi Agribisnis INSTIPER Yogyakarta, 2025)
Brown Planthopper pest attacks are problem faced by farmer in the paddy cultivation process. In this problem, farmer used Beauveria Bassiana wich was introduced by agricultultural extension workers as solution from Brown Planthopper attacks. This research aims to analyze the Beauveria Bassiana innovation adoption process through the stages of knowledge, persuasion, decision, implementation and confirmation. This research location in Wirowongso Village, Ajung District, Jember Regency. Determining the research area using Purposive Method with 6 farmer as respondent and using qualitative descriptive approach. Data collection was carried out using 3 methods, namely observation, interviews and documentation. Data analysis used the Miles and Hubberman qualitative analysis model. The results of the analysis show that in the process of Beauveria Bassiana adoption, there are five stages, namely the stage of knowledge, persuasion, decision, implementation, and confirmation. The result of diffusion process, it shows that the adoption process only occurs in three categories of adopters, namely innovators (heads of farmer groups), early adopters (farmer group secretaries) and early majority (farmers) Keywords: Adoption; innovation; Beauveria Bassiana; Brown Planthopper ABSTRAK Serangan hama wereng coklat merupakan masalah yang dihadapi petani dalam proses budidaya tanaman padi. ​​Dalam masalah ini, petani menggunakan Beauveria Bassiana yang diperkenalkan oleh petugas penyuluh pertanian sebagai solusi dari serangan wereng coklat. Penelitian ini bertujuan untuk menganalisis proses adopsi inovasi Beauveria Bassiana melalui tahapan pengetahuan, persuasi, keputusan, implementasi dan konfirmasi. Lokasi penelitian ini di Desa Wirowongso, Kecamatan Ajung, Kabupaten Jember. Penentuan daerah penelitian menggunakan Metode Purposive dengan 6 orang petani sebagai responden dan menggunakan pendekatan deskriptif kualitatif. Pengumpulan data dilakukan dengan menggunakan 3 metode, yaitu observasi, wawancara dan dokumentasi. Analisis data menggunakan model analisis kualitatif Miles dan Hubberman. Hasil analisis menunjukkan bahwa dalam proses adopsi Beauveria Bassiana terdapat lima tahapan, yaitu tahap pengetahuan, persuasi, keputusan, implementasi, dan konfirmasi. Hasil proses difusi menunjukkan bahwa proses adopsi hanya terjadi pada tiga kategori adopter yaitu inovator (ketua kelompok tani), early adopter (sekretaris kelompok tani) dan early mayoritas (petani). Kata Kunci: hama wereng coklat; adopsi, inovasi; Beauveria Bassiana